Interactions between autologous T cell clones. - Naor, D; Essery, G; Tarcic, N; Kahan, M; Feldmann, M (1990)
A human CD4 clone (Mx9/9) using the V beta 8 receptor was used as antigen to generate autologous clones (termed anti-Mx9/9 clones) which proliferate in response to this clone, but not other autologous clones. This was used as an experimental model to explore the specific interactions between autologous T cells. Anti-HLA-DR monoclonal antibodies inhibited the response of the anti-Mx9/9 clones, suggesting that these clones recognize their target antigen in association with HLA-DR. Because of the specificity of the anti-Mx9/9 clones for the initiating clone (Mx9/9), but not any other autologous V beta 8- or V beta 8+ CD4 clones, the target antigen seems to be part of the T cell receptor, but not V beta 8 itself. However, the anti-Mx9/9 clones responded also to the autologous EBV line, and thus the target antigen is not known. The regulatory activity of the anti-Mx9/9 clones was assayed by coculture with their target clone. A variety of responses were seen, both inhibitory and stimulatory, which varied depending on the "conditions" of the T cell used. These results suggest that T cells interact in a complex network, perhaps as complex as the regulatory interactions between antibody molecules and B cells.